2016
DOI: 10.1080/00071668.2016.1156648
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effectiveness of head only and back-of-the-head electrical stunning of chickens

Abstract: The study assesses the effectiveness of reversible head-only and back-of-the-head electrical stunning of chickens using 130–950 mA per bird at 50 Hz AC.Three trials were conducted to compare both stunning systems: (a) behavioural assessment of return of consciousness, (b) insensibility to thermal pain, and (c) assessment of return of brain activity with visually evoked potentials (VEPs).Assessment of behaviour suggested that the period of unconsciousness following head-only electrical stunning was shorter in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Apnoea after stunning has been associated with damage to the medulla and reticular formation. The absence of the nictitating membrane reflex is associated with brainstem dysfunction, and the lack of neck tension relates to loss of CNS control of muscle tone (Gibson et al, 2016, Terlouw et al, 2016.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Apnoea after stunning has been associated with damage to the medulla and reticular formation. The absence of the nictitating membrane reflex is associated with brainstem dysfunction, and the lack of neck tension relates to loss of CNS control of muscle tone (Gibson et al, 2016, Terlouw et al, 2016.…”
Section: Tablementioning
confidence: 99%
“…There are many welfare concerns regarding waterbath stunning of poultry, due to the risks of pre-stun shocks, suboptimum stuns, stress and pain during inversion and suspension from shackles, variations in electrical current delivered to birds in multi-bird waterbath stunners and aspiration of waterbath water (EFSA, 2014, Hindle et al, 2010. Meanwhile research on head-only constant voltage electrical stunning of end of lay hens (Gallus g domesticus) reported that for some birds the period of induced insensibility only lasted 9 seconds (8.5 -31.5) seconds (Gibson et al, 2016). This could result in some hens recovering from the stun prior to, or during the bleeding process, resulting in significant pain and distress.…”
Section: Introductionmentioning
confidence: 99%
“…A significant proportion of these birds are slaughtered and processed by small-scale seasonal producers using head-only constant voltage stunning equipment [15]. With a widespread acknowledgment of the limitations of currently used constant voltage head-only electrical stunning systems [1,16] there has been a refocus on the captive bolt as an alternative method for small scale seasonal turkey producers.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the left and right hemispheres were pooled to aid analysis. Severity of tissue damage to specific brain regions Immediately after shooting, all animals were assessed for clinical signs of sensibility, including the presence or absence of tonic and clonic convulsions, rhythmic breathing, nictitating membrane reflex, eyeball rotation, nystagmus, neck tension, and beak tension [1,4]. Eye-based reflexes were tested on both eyes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation